Improved Production of ε-Poly-L-Lysine in Streptomyces albulus Using Genome Shuffling and Its High-Yield Mechanism Analysis - Liu, Yongjuan; Wang, Kaifang; Pan, Long; Chen, Xusheng (Frontiers in Microbiology, 2022)
ε-Poly-L-lysine (ε-PL), a natural food preservative, has recently gained interest and mainly produced by Streptomyces albulus. Lacking of efficient breeding methods limit ε-PL production improving, knockout byproducts and increase of main product flux strategies as a logical solution to increase yield. However, removing byproduct formation and improving main product synthesis has seen limited success due to the genetic background of ε-PL producing organism is not clear. To overcome this limitation, random mutagenesis continues to be the best way towards improving strains for ε-PL production. Recent advances in Illumina sequencing opened new avenues to understand improved strains. In this work, we used genome shufﬂing on strains obtained by ribosome engineering to generate a better ε-PL producing strain. The mutant strain SG-86 produced 144.7% more ε-PL than the parent strain M-Z18. Except that SG-86 displayed obvious differences in morphology and ATP compared to parent strain M-Z18. Using Illumina sequencing, we mapped the genomic changes leading to the improved phenotype. Sequencing two strains showed that the genome of the mutant strain was about 2.1 M less than that of the parent strain, including a large number of metabolic pathways, secondary metabolic gene clusters, and gene deletions. In addition, there are many SNPs (single nucleotide polymorphisms) and InDels (insertions and deletions) in the mutant strain. Based on the results of data analysis, a mechanism of ε-PL overproduction in S. albulus SG-86 was preliminarily proposed. This study is of great significance for improving the fermentation performance and providing theoretical guidance for the metabolic engineering construction of ε-PL producing strains.